Never look back - Gaylin, Alison (William Morrow, an imprint of HarperCollinsPublishers, 2019)
For thirteen days in 1976, teenage murderers April Cooper and Gabriel LeRoy terrorized Southern California's Inland Empire, killing a dozen victims before perishing themselves in a fire... or did they? More than 40 years later, twentysomething podcast producer Quentin Garrison blames his troubled upbringing on the murders. And after a shocking message from a source, he has reason to believe April Cooper may still be alive. Meanwhile, New York City film columnist Robin Diamond is coping with rising doubts about her husband and terrifying threats from internet trolls. But that's nothing compared to the outrageous phone call she gets from Quentin... and a brutal home invasion that makes her question everything she ever believed in. Is Robin's beloved mother a mass murderer? Is there anyone she can trust? Told through the eyes of those destroyed by the Inland Empire Killings<U+2014>including Robin, Quentin, and a fifteen-year-old April Cooper<U+2014>Never Look Back asks the question: How well do we really know our parents, our partners<U+2014>and ourselves?